THE FEATHER-TAILED GLIDER (Acrobates pygmeus) IN NEW GUINEA - Kristofer M. Helgen (BRIN Publishing (Penerbit BRIN), 2003)
Acrobates pygmeus is a small arboreal marsupial thought to be restricted to eastern Australia, from southeastern South Australia to the tip of Cape York Peninsula in northern Queensland. Here I discuss the possibility that the species also occurs in New Guinea, based on two poorly-localized museum specimens (in London and Stockholm) supposedly collected from that island.